Antifungal activity of thymol against the main fungi causing pomegranate fruit rot by suppressing the activity of cell wall degrading enzymes. (1st May 2022) - Ranjbar, Azam; Ramezanian, Asghar; Shekarforoush, Shahram; Niakousari, Mehrdad; Eshghi, Saeid
Abstract: Postharvest rot of pomegranate fruits due to fungal infections causes the loss of a significant amount of fruit. In this study, the antifungal effects of thymol on the growth of Aspergillus niger ( A. niger ) and Penicillium commune ( P. commune ) were investigated. Molecular sequence analysis of internal transcribed spacer (ITS) gene was used to identify fungal species. ITS of rDNA amplified by polymerase chain reaction (PCR), sequenced and after basic local alignment search, it was registered in GenBank database. The minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) of thymol for both fungi were 250 and 500 μg mL −1, respectively. Scanning electron microscopy (SEM) in A. niger colony showed cell deformation due to destruction of the cell membrane and loss of cell wall strength at 250 μg mL −1 after 168 h. Evaluation of P. commune cell morphology showed that thymol at 250 μg mL −1 caused superficial wrinkles, bifurcation of hyphal apex and no spore production was observed. Thymol suppressed fungal growth by reducing cellulase and pectinase activity. The smallest cellulase and pectinase halo diameter was found at 125 μg mL −1 of thymol . Thymol at 500 μg mL −1 had a similar fungicidal effect compared with thiabendazole (1500 μg mL −1 ). Highlights: Thymol suppresses Penicillium commune and Aspergillus niger growth. The minimum inhibitory concentration of thymol was 250 μg mL −1 . Scanning electron microscopy showed colony deformation due to cell membrane destruction. Thymol suppressed fungal growth by reducing cellulase and pectinase activity.